OPTIMIZING EDUCATIONAL ADMINISTRATION GOVERNANCE IN SUPPORTING QUALITY EDUCATION MANAGEMENT AT MTS HIDAYATUL MUBTADIIN MUKOMUKO - Ahmad Arifin; Fauzi Fauzi; Salamun Salamun; Iis Maisaroh (YHMM PUBLISHING, 2026)
This study aims to analyze the optimization of educational administration governance in supporting quality educational management at MTs Hidayatul Mubtadiin Mukomuko. The research employed a descriptive qualitative approach with a case study design to obtain an in-depth understanding of the implementation of educational administration within the madrasah environment. Data were collected through observations, in-depth interviews, and documentation involving the principal, three homeroom teachers, six parents, and eight students from different grade levels. The findings reveal that educational administration governance has played a significant role in improving the effectiveness of educational management, particularly in academic administration, student data management, coordination among educational staff, and educational services. The principal actively conducted supervision and evaluation of administrative processes, while teachers contributed to managing learning administration and academic reporting. Parents and students also perceived the administrative services as sufficiently responsive and supportive of educational activities. However, the study identified several challenges, including limited digitalization of administrative systems and manual data management practices, which affected administrative efficiency and service quality. The study concludes that strengthening educational administration governance through technology-based administrative systems, organizational coordination, and continuous evaluation can significantly improve the quality of educational management. This research contributes theoretically to educational management studies and practically provides recommendations for improving administrative governance in Islamic educational institutions.